Changes in Traditional Technology of Asphalt Concrete Mixture due to Feedback of Power and Technological Reconstruction of Production - V. N. Romaniuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2003)
The paper considers a new technology concerning the application of bitumen binder for production of asphalt concrete mixture. This technology radically changes the structure of asphalt and concrete production. The proposed technology has been elaborated in the process of modernization of thermal and power supply pertaining to asphalt concrete mixture production.